2016
DOI: 10.3329/ajmbr.v1i3.26468
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of nutritional composition and heavy metal content in some edible mushroom varieties collected from different areas of Bangladesh

Abstract: Four edible mushroom species (Pleurotus ostreatus, Agaricus bisporus, Volvariella volvacea, Ganoderma lucidum) from different locations of Bangladesh, were analysed for their protein and metal content profile (K, Na, Fe, Cu, Zn, Mn, Cr, Pb, As and Cd). Trace metals were determined by atomic absorption spectrophotometer, Na and K by flame emission spectrophotometer and protein by micro Kjeldhal method. All element concentrations were determined on a dry weight basis. The protein content of mushrooms varied from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 21 publications
1
4
4
Order By: Relevance
“…The Cr concentrations of mushrooms in this study were much less than those in a previously-published database ( Table 2 ) on cultivated mushrooms except a study in Bangladesh [ 31 ]. The highest concentration of chromium (63.0 mg/kg, dw) was observed in Mexico [ 39 ] in P. ostreatus mushroom and the lowest (4.06 mg/kg, dw) was in A. bisporus in the same country ( Table 2 ).…”
Section: Resultscontrasting
confidence: 72%
See 3 more Smart Citations
“…The Cr concentrations of mushrooms in this study were much less than those in a previously-published database ( Table 2 ) on cultivated mushrooms except a study in Bangladesh [ 31 ]. The highest concentration of chromium (63.0 mg/kg, dw) was observed in Mexico [ 39 ] in P. ostreatus mushroom and the lowest (4.06 mg/kg, dw) was in A. bisporus in the same country ( Table 2 ).…”
Section: Resultscontrasting
confidence: 72%
“…The concentrations of Cu in this study (6.7–24.3 mg/kg, dw) were slightly higher than P. sajor-kaju , a cultivated mushroom of Turkey [ 41 ] but highest concentration was observed in Mexico [ 39 ]. However, P. ostreatus of another study in Bangladesh obtained higher Cu concentration [ 31 ] than the same one of this study. A. bisporus in Australia [ 40 ] and Hungary [ 42 ] contained about four times higher Cu than this investigation ( Table 2 ).…”
Section: Resultscontrasting
confidence: 68%
See 2 more Smart Citations
“…It was observed that the lowest and highest mushroom protein contents were obtained respectively with the substrates with lowest (hors-ban: 0-100 with 1.6% N) and highest (hors-chic: 0-100 with 2.3% N) nitrogen contents. Even with the same species, values obtained values of protein content were lower than those reported by Sadiq et al (2008): 11.01 %, Muszyńska et al (2011): 25%, Mohiuddin et al (2015): 17.7%-24.7% and Ahlavat et al (2016): 29.14 % in different growing substrates, while they were in the range indicated by Chang and Miles (2004): 3.5 to 4%.…”
Section: Resultscontrasting
confidence: 62%